2017
DOI: 10.1136/bjsports-2016-097372.43
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Nordic Hamstring and Hip Extension Exercises on Hamstring Architecture and Morphology: Implications for Injury Prevention

Abstract: 31The architectural and morphological adaptations of the hamstrings in response to training  Hip extension training promotes more hypertrophy in the biceps femoris long head and semimembranosus than the Nordic hamstring exercise, which preferentially develops the semitendinosus and the short head of biceps femoris.4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
111
3
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(125 citation statements)
references
References 8 publications
4
111
3
7
Order By: Relevance
“…Therefore, we included 10 studies in this systematic review. [38][39][40][41][42][43][44][45][46][47] Figure 1 shows the selection process.…”
Section: Results Of Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, we included 10 studies in this systematic review. [38][39][40][41][42][43][44][45][46][47] Figure 1 shows the selection process.…”
Section: Results Of Study Selectionmentioning
confidence: 99%
“…The methodologic quality assessment is provided in Figure 2 and Table 2. Five studies [38][39][40]45,47 reported the assessors were blinded. Only 4 studies demonstrated no differences in outcome measurements 42,44,45,47 or population characteristics 38,40,44,47 across study groups before the intervention.…”
Section: Methodologic Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations